A platinum catalyst deposited on a zirconia support for the design of lithium–oxygen batteries with enhanced cycling ability. Issue 86 (16th October 2017) - Bae, Seongjun; Geun Yoo, Young; Park, Jongseok; Park, Soomin; Nam, Inho; Woo Han, Jeong; Yi, Jonghoep
Abstract : A platinum catalyst deposited onto a zirconia support with oxygen-defective sites is developed for the stabilization of the discharge product of lithium–oxygen batteries. Abstract : A platinum catalyst supported on zirconia is proposed as a cathode in lithium–oxygen batteries. Experimental and theoretical studies show that zirconia suppresses the side-reactions of the intermediate (O2 − ) and the final product (Li2 O2 ) by the stabilization of their reactivity. Thus, it is able to enhance the reversibility during charge/discharge in lithium–oxygen batteries.